2003
DOI: 10.1046/j.1351-0754.2003.0567.x
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of greenhouse gases between soil and atmosphere: interactions of soil physical factors and biological processes

Abstract: Summary This review examines the interactions between soil physical factors and the biological processes responsible for the production and consumption in soils of greenhouse gases. The release of CO2 by aerobic respiration is a non‐linear function of temperature over a wide range of soil water contents, but becomes a function of water content as a soil dries out. Some of the reported variation in the temperature response may be attributable simply to measurement procedures. Lowering the water table in organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
500
6
20

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 884 publications
(581 citation statements)
references
References 67 publications
29
500
6
20
Order By: Relevance
“…The elevated rates we observed reflect environmental conditions conducive to denitrification, i.e. low DO (<1 mg O 2 /L; Table 3) plus a highly enriched organic matter sediment (Table 2) and optimum sediment-water contact time within the confined lysimeter environment (Hill 1996;Fennessy and Cronk 1997;Hoffmann et al 2000;Smith et al 2003). The observed high denitrification rates could be attributed to the elevated DEA values (Table 4) in the wetland soils (Groffman et al 1999).…”
Section: Preliminary Testing Of the Push-pull Technique Within A Confmentioning
confidence: 64%
See 4 more Smart Citations
“…The elevated rates we observed reflect environmental conditions conducive to denitrification, i.e. low DO (<1 mg O 2 /L; Table 3) plus a highly enriched organic matter sediment (Table 2) and optimum sediment-water contact time within the confined lysimeter environment (Hill 1996;Fennessy and Cronk 1997;Hoffmann et al 2000;Smith et al 2003). The observed high denitrification rates could be attributed to the elevated DEA values (Table 4) in the wetland soils (Groffman et al 1999).…”
Section: Preliminary Testing Of the Push-pull Technique Within A Confmentioning
confidence: 64%
“…Both surface water and subsurface water had low DO levels (<1 mg O 2 /L; Table 3), suggesting that anaerobic conditions favourable for denitrification (Smith et al 2003;Zaman et al 2008b) were prevalent in this wetland. Various workers (Tiedje 1988;Patrick and Jugsujinda 1992;Achtnich et al 1995;Blicher-Mathiesen and Hoffmann 1999) have reported that NO 3 À reduction occurs mainly when subsurface water DO falls below 0.5-1.6 mg O 2 /L.…”
Section: Wetland Sediment Physical and Chemical Characteristics And Pmentioning
confidence: 99%
See 3 more Smart Citations